Evaluation of the impact and implementation of a national clinical programme for the management of self-harm in hospital emergency departments: study protocol for a natural experiment. Issue 12 (24th December 2021) - Griffin, Eve; McHugh, Sheena M; Jeffers, Anne; Gunnell, David; Arensman, Ella; Perry, Ivan J; Cully, Grace; McElroy, Brendan; Maxwell, Margaret; Chang, Shu-Sen; Ruane-McAteer, Eimear; Corcoran, Paul
Abstract : Background: A National Clinical Programme for the Management of Hospital-Presenting Self-Harm (NCP-SH) was introduced in Ireland in 2014. This involved the development of a model of care to standardise the management of self-harm in emergency departments, to be delivered by dedicated clinical nurse specialists. The core components of the programme were to: ensure an empathic and timely response, conduct a biopsychosocial assessment, involve family members in assessment and discharge planning, and provide a bridge to next care. The overall aim of the programme was to reduce the rate of repeat self-harm. This multistage study will evaluate the impact of the NCP-SH on hospital-presenting self-harm and to identify determinants influencing its implementation. Methods: Employing a sequential mixed methods design, the first stage will use data from the National Self-Harm Registry Ireland to examine the impact of the NCP-SH on self-harm repetition, along with other aspects of care, including provision of psychosocial assessments and changes in admissions and postdischarge referrals. A cost-effectiveness analysis will assess the cost per repeat self-harm attendance avoided as a result of the NCP-SH. The second stage will identify the influences of implementation fidelity—adherence to the programme's core components—using a combination of document analysis and semistructured interviews with staff of the programme, guided by the Consolidated Framework for Implementation Research. Ethics and dissemination: This study has received full ethical approval and will run until August 2023. This study is novel in that it will identify important factors influencing successful implementation of complex programmes. It is expected that the findings will provide important learnings for the integration of mental health services in general hospital settings and will be disseminated via peer-review publications along with reports for clinicians and policy-makers.